World Cereal Nitrogen Use Efficiency Trends: Review and Current Knowledge - Omara, Peter; Aula, Lawrence; Oyebiyi, Fikayo; Raun, William R. (Agrosystems, Geosciences & Environment, 2019)
Two decades ago, world cereal nitrogen use efficiency (NUE) was documented at 33%. Since then, research addressing NUE has advanced. However, there are no current estimates to communicate whether or not research efforts and recent advances have contributed to improved NUE. With the apparent trends for increasing greenhouse gases, NUE values could be used as a management tool for agronomic and environmental sustainability. Our objective was to provide current estimates and trends of NUE for the world and selected countries for cereal crops cultivated in relatively large quantities. Data from the Food and Agriculture Organization (www.fao.org/faostat) website were used to compute NUE. The difference method was employed to derive NUE and trends. Results indicated that cereal NUE in 2015 was 35, 41, 30, and 21% for the world, the United States, China, and India, respectively. Compared with 33% reported in 1999, there was insignificant trend of increase (r2 = 0.01) from 2002 to 2015 for cereal world NUE (p > 0.05). Low NUE for China and India was due to high N consumption. A slight improvement for the United States from 31% in 2002 to 41% in 2015 (r2 = 0.20) could be a result of using improved cultivars and precision crop management. Increasing cereal NUE in the United States echoes the value of new technologies and the heightened importance of the environment. Recognizing year-to-year variability in N fertilizer requirement and implementing a systematic approach that combines agronomic recommendations with improved crop varieties could further improve NUE.
Keywords: World Cereal Nitrogen; Efficiency; Knowledge